CYTOTOXIC ACTIVITY OF KASUMBA FLOWER ETHANOL EXTRACT TURATE (Carthamus tinctorius Linn.) AGAINST THE LINE OF CANCER CELLS T47D BREASTS - Fadhliyah Malik; Muhammad Hajrul Malaka; Adryan Fristiohady; Wahyuni Wahyuni; Rini Hamsid; Sahidin Sahidin; Annisa Fatinah Gani (Jurnal Farmasi Sains dan Praktis, 2021)
Breast cancer is a type of cancer with a high prevalence in the world and causes death in women. Chemotherapy is one type of treatment that is widely used. However, the problems of chemotherapy drugs such as side effects, drug resistance and inadequate efficacy. So, to overcome these problems, many natural ingredients have been explored to find anticancer agents that are expected to have good efficacy with minor side effects. Kasumba turate flowers (Carthamus tinctorius Linn.) is a plant from the Asteraceae tribe which is known to contain secondary metabolites with pharmacological activity as anticancer. This study aims to determine the types of secondary metabolites and the cytotoxic activity of the ethanolic extract of Kasumba turate flower against the T47D breast cancer cell line using the MTT assay method. Kasumba turate flower extract was obtained by maceration using 96% ethanol solvent, so that a concentrated extract with a weight of 107.8 grams was obtained with a yield value of 10.81%. The extract obtained was then subjected to a phytochemical screening test using the tube method and the results are alkaloids, flavonoids, tannins, and terpenoids. In the cytotoxic activity test, the test samples were varied into 7 concentration series, namely 10, 50, 100, 200, 400, 800 and 1000 ppm. The positive control used was 5-Fu. Cytotoxic parameter (IC50 value) was determined using GraphPad Prism and obtained IC50 5-Fu value of 65.88 ppm with active category while IC50 of the test sample was 157.3 with moderately active category as anticancer breast.